2013
DOI: 10.15376/biores.9.1.685-703
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Municipal Biowaste Biochar on Greenhouse Gas Emissions and Metal Bioaccumulation in a Slightly Acidic Clay Rice Paddy

Abstract: A field trial was performed to investigate the effect of municipal biowaste biochar (MBB) on rice and wheat growth, metal bioaccumulation, and greenhouse gas emissions in a rice paddy in eastern China. MBB was amended in 2010 before rice transplanting at rates of 0 and 40 t ha -1 in a field experiment lasting one cropping year. MBB soil amendment significantly increased soil pH, total soil organic carbon, and total nitrogen. The growth and grain yield of rice and wheat was not affected with MBB application at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Care was taken not to disturb soil within the pans. Following pan installation, greenhouse gas emissions were measured regularly from April 21st to September 16th (days 0, 14,22,29,38,45,50,60,72,79,86,93,109, 120 and 148). These dates reflect more frequent measurements during periods of expected high GHG emission rates directly following fertilizer application and rainfall.…”
Section: Field Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Care was taken not to disturb soil within the pans. Following pan installation, greenhouse gas emissions were measured regularly from April 21st to September 16th (days 0, 14,22,29,38,45,50,60,72,79,86,93,109, 120 and 148). These dates reflect more frequent measurements during periods of expected high GHG emission rates directly following fertilizer application and rainfall.…”
Section: Field Studymentioning
confidence: 99%
“…Only ten field studies reported significant reductions in N 2 O emissions, five reported no significant impact and one reported a significant increase. Furthermore, all but two of the studies reporting significant changes in N 2 O emissions measured ≤12 months after biochar application and all studies focused on only one cropping system [32][33][34][35][36][37][38][39][40][41][42]. Recent evidence suggests that biochars' impacts on N 2 O emissions may change over time as biochar ages, highlighting the need for studies comparing fresh and aged biochar, especially at the field scale [43].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that biochar application enhances GHG emission. Biochar application pyrolyzed at 350°C-550°C from wheat straw at 40 t•ha − 1 , with and without N heightened the CH 4 emission by 34% and 41%, respectively [26], CO 2 emission by 12% [29] and 44.9% from municipal biowaste biochar in rice [123]. It was also reported that 24 t and 48 t•ha − 1 of biochar applied from pyrolysis (500°C) of wheat straw increased the emission of N 2 O by 150% and 190%, respectively [124].…”
Section: Effects On Ghg Emissionmentioning
confidence: 99%
“…Of these studies, ten reported significant reductions in N 2 O emissions at the field scale, five reported no significant impact, and one reported a significant increase. Furthermore, all but two of the cited studies reporting significant changes in N 2 O emissions measured ≤12 months after biochar application, and all studies focused on a single cropping system (Zhang et al, 2010(Zhang et al, , 2012(Zhang et al, , 2013Scheer et al, 2011;Bian et al, 2014;Felber et al, 2014;Pandey et al, 2014;Shen et al, 2014;Van Zwieten et al, 2014;Case et al, 2014…”
Section: Introductionmentioning
confidence: 99%